Analisis Tuturan Deddy Corbuzier dalam Podcast “Smart People” di Media Youtube - Deri Wan Minto; Dadang S. Anshori; Vismaia S. Damaianti; Ananda Putriani (Balai Bahasa Sulawesi Selatan, 2024)
Advances in technology develop aspects of digital virtual communication. Deddy Corbuzier, the YouTube Channel owner, utilizes digital virtual media for Podcast shows. Problems arise from communication that tends to be straightforward, assertive, and no-nonsense. In the communication process, the other person failed to understand. This study aims to describe Deddy Corbuzier's communication on the YouTube channel. Qualitative research uses a descriptive form of analysis. The analysis technique used was data reduction, data presentation, and conclusions drawn at the end of the study. The research results are essential for Podcast hosts on YouTube Channels to be better and friendlier in choosing language strategies in public spaces. Specifically, the analysis of Deddy Corbuzier's speech in the 'Smart People' podcast on YouTube media should have a socially friendly language order. This is because the YouTube Channel